Weber numbers at various stages of water projectile transformation during free fall in air; Technical Physics Letters; Vol. 41, iss. 10 - Volkov R. S. Roman Sergeevich; Kuznetsov G. V. Geny Vladimirovich; Kuibin P. A.; Strizhak P. A. Pavel Alexandrovich (2015, 2015)
Title screen